MENELUSURI JEJAK KEBIJAKAN PUBLIK: TINJAUAN LITERATUR TERHADAP PENANGANAN STUNTING DI KABUPATEN SIDOARJO - Mulyani, Sri (Jurnal Progress Administrasi Publik, 2024)
This research aims to analyze public policies regarding stunting management in Sidoarjo Regency, focusing on factors influencing the success or failure of their implementation. The research method employed is a qualitative approach using literature review or library research. Data are obtained through collecting information from scientific papers and relevant literature sources. Data analysis is conducted inductively to understand meanings, explore uniqueness, and find hypotheses related to public policy on stunting management in Sidoarjo Regency. The discussion covers government and stakeholder efforts to address stunting, including supplementary feeding programs, exclusive breastfeeding, and clean and healthy living education, as well as innovative online applications. Nevertheless, these interventions require active participation from the community. The role of Posyandu cadres is pivotal in conveying information and motivating families to adopt good nutritional practices. Investment in enhancing the knowledge and skills of Posyandu cadres is necessary to ensure their effectiveness. Cross-sector collaboration is also crucial for the success of stunting management programs. Periodic evaluations of existing programs are expected to help identify successes and challenges faced. The research findings indicate positive progress but require further efforts. With a comprehensive approach, it is hoped that the stunting rate can continue to decline and improve the quality of life for children. This research is expected to contribute to enhancing the effectiveness of policies and programs for stunting management and the welfare of the community in Sidoarjo Regency.   Keywords: Public; Policy; Stunting